First report of ivermectin resistance in natural infected Foals by Parascaris spp. in Tiaret, Algeria - Ammar Selles Sidi Mohammed; Ait Amrane Amar; Kouidri Mokhtaria; Belhamiti Belkacem Tahar; Belmedjahad Mustapha; Bouchentouf Keltoum; Kadi Marwa; Mihoubi Amel (Revista Científica)
Equine parascarosis is a Worldwide endoparasitosis, caused by Parascaris spp., affecting mainly younger horses. This disease is considered as the most pathogenic parasitosis of young horses. In Algeria, no knowledge of the resistance of Parascaris spp. to Ivermectin is published. For this reason, the present study aims to evaluate the frequency of Parascaris spp. and the anthelmintic efficacy of Ivermectin and Fenbendazole against this parasite in a foal population in Tiaret, Algeria. Ninety–one foals were examined for the presence of Parascaris spp. from two stud farms. Among the positive, thirty–two faols were treated with Ivermectin formulations (Ivoral® and Eqvalan®) and Fenbendazole (Funcur®) at their recommended dosages. Fecal egg count reduction testing (FECRT) was used to determine the efficacy of each anthelmintic. Parascaris spp. was detected in 61 foals (67.03%). Decreased efficacy (reduction of Parascaris spp. fecal egg counts by less than 90%) was found for the two Ivermectin formulations (46.45% for Ivoral® and 70.29% for Eqvalan®). Nevertheless, fenbendazole showed 100% efficacy in all foals sampled in this study. These first data indicate that Ivermectin–resistant Parascaris spp. populations are present on horse farms in Algeria. Findings from this study can be used to create a more sustainable approach for parasite control programs.